2014
DOI: 10.1007/s00467-013-2724-0
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from twice- to once-daily tacrolimus in pediatric kidney recipients: a pharmacokinetic and bioequivalence study

Abstract: BackgroundThe objectives of this study were to investigate pharmacokinetic and pharmacogenetic parameters during the conversion on a 1:1 (mg:mg) basis from a twice-daily (Prograf) to once-daily (Advagraf) tacrolimus formulation in pediatric kidney transplant recipients.MethodsTwenty-four-hour pharmacokinetic profiles were analyzed before and after conversion in 19 stable renal transplant recipients (age 7–19 years). Tacrolimus pharmacokinetic parameters [area under the concentration-time curve (AUC0–24), minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Studies in adult LT patients support the use of once‐daily extended‐release tacrolimus (Astagraf XL, Advagraf) with a similar safety and efficacy as standard tacrolimus . Data from small groups of pediatric patients who had kidney or living related donor LT show that both formulations were bioequivalent . There was a mild decrease in the area under the concentration‐time curve and whole‐blood concentration after conversion in pediatric renal recipients which may require closer drug level monitoring during the conversion period .…”
Section: Specific Immunosuppressionmentioning
confidence: 99%
“…Studies in adult LT patients support the use of once‐daily extended‐release tacrolimus (Astagraf XL, Advagraf) with a similar safety and efficacy as standard tacrolimus . Data from small groups of pediatric patients who had kidney or living related donor LT show that both formulations were bioequivalent . There was a mild decrease in the area under the concentration‐time curve and whole‐blood concentration after conversion in pediatric renal recipients which may require closer drug level monitoring during the conversion period .…”
Section: Specific Immunosuppressionmentioning
confidence: 99%
“…Tacrolimus is a new prolonged-release once-daily formulation of tacrolimus. Limited data (mainly pharmacokinetic data) were reported in children who had liver and renal transplants 11 12. It is recommended that patients receiving stable treatment with tacrolimus twice daily can be switched to tacrolimus once daily, on a daily milligram-for-milligram basis, followed with close TDM.…”
Section: Tacrolimusmentioning
confidence: 99%
“…Among pediatric kidney transplant recipients, AUC and trough were noted to decrease after conversion to once-daily tacrolimus 11,12. These differences were statistically significant in a PK study involving 34 patients11 and not statistically significant in another study involving 19 patients 12. C max was also not significantly different between formulations and CYP3A5 genotypes 12.…”
Section: Once-daily Tacrolimus: Dosing and Pharmacokineticsmentioning
confidence: 87%
“…These differences were statistically significant in a PK study involving 34 patients11 and not statistically significant in another study involving 19 patients 12. C max was also not significantly different between formulations and CYP3A5 genotypes 12. PK studies conducted on 19 stable lung transplant patients converted to once-daily tacrolimus showed that the bioavailability of tacrolimus is similar with once- and twice-daily formulations.…”
Section: Once-daily Tacrolimus: Dosing and Pharmacokineticsmentioning
confidence: 88%
See 1 more Smart Citation